2-(3-Ethylsulfanyl-5-phenyl-1-benzofuran-2-yl)acetic acid - Choi, Hong Dae (International Union of Crystallography, 2009)
The title compound, C(18)H(16)O(3)S, crystallizes with two symmetry-independent molecules in the asymmetric unit. The phenyl rings are rotated out of the benzofuran planes, making dihedral angles of 43.38 (7) and 56.13 (6)° in the two molecules. The carboxyl groups are involved in inversion-related intermolecular O—H⋯O hydrogen bonds, which link the molecules into centrosymmetric dimers. These dimers are further packed into stacks along the b axis by weak non-classical intermolecular C—H⋯O hydrogen bonds. The crystal structure also exhibits intermolecular C—H⋯π interactions, and two aromatic π–π interactions between the furan rings of neighbouring benzofuran systems; the centroid–centroid distances are 3.500 (3) and 3.605 (3) Å.